Social Practices, (Des)protection of Environmental Rights and Strategic Actions - Ruscheinsky, Aloisio (2019)
The study presents some aspects of the discussion about interfaces of social practices, water resources and social welfare. Data of the diagnostic on the effects of the dikes against floods are used, as well as the perception of the process that the population has, in relation to environmental issues. The article is the result of a broader investigation, which maps the multiple and diversified attitudes of the population in regard to the discussion of the environmental policies of care and preservation against its impacts and environmental risks. Part of the impacts of floods can be avoided with social practices consistent with protection rights. Public policies in the face of the environmental crisis yearn to mitigate the social effects of this process, which intensifies in the consumer society. In conclusion, the study verifies that there is a tension between rights to social and environmental protection.